PENGARUH CITRA MEREK, HARGA, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PADA TOMORO COFFEE SEMARANG - Musfiyana, Risma; Sasono, Eko; Subekti, Heni (Sekolah Tinggi Ilmu Ekonomi Semarang, 2025)
In the midst of increasingly fierce coffee industry competition, coffee shop businesses in Indonesia are faced with big challenges to remain relevant and attractive to customers. Dependence on quality raw materials, price competitiveness and promotion of needs to present special customer experiences become crucial factors.Tomoro Coffee comes as an example of how a coffee brand can developrapidly in a short time. With the support of technology, innovative strategies, and commitment to product quality, Tomoro Coffee won the hearts of Indonesian consumers. With the support of technology, innovative strategies, and commitment to product quality, Tomoro Coffee won the hearts of Indonesian consumers. Founded in August 2022 by Xing Wei Yuan, Tomoro Coffee now has more than 200 outlets throughout Indonesia.This study aims to determine the effect of brand image, price, and promotion on purchasing decisions at Tomoro Coffee in the city of Semarang. The population in this study was Tomoro Coffee customers in the city of Semarang. The sampling technique used by purposive sampling with 100 respondents is determined using the lemeshow formula. Research data were analyzed using multiple regression methods. The results showed that the brand image had an influence on purchasing decisions, prices had an influence of purchasing decisions, then promotion also had an influence on purchasing decisions.